A bifunctional water electrolysis catalyst and its preparation method and application
By embedding CeO2 in situ on NiFe-LDH and loading it onto the foam metal, NiFe-LDH/CeO2/foam metal catalyst was prepared, which solved the problems of high precious metal costs and poor performance of NiFe-LDH in the prior art. The bifunctional and low-cost characteristics of electrolytic water catalyst are realized.
Patent Information
- Application Number
- CN202311024813.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-08-15
AI Technical Summary
Among the existing electrocatalytic water decomposition technology, precious metal electrocatalysts have high cost and are difficult to develop. NiFe-LDH materials have poor performance when catalyzing HER and are difficult to act as dual-function electrolytic catalysts for OER and HER.
Through hydrothermal reaction, CeO2 is embedded in situ on NiFe-LDH and loaded onto the foam metal to prepare NiFe-LDH/CeO2/foam metal catalyst to control the molar ratio of nickel source, iron source, CeO2 and NiFe-LDH /Fluid ratio of /CeO2, binder, and dispersant to achieve the bifunctionality of the catalyst.
The catalyst can have excellent OER and HER catalytic activity and stability at the same time, reduce the cost of hydrogen production by electrolyzing water, and has the characteristics of low cost and high activity.
Smart Images

Figure CN116905039B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemistry, and in particular to a bifunctional water electrolysis catalyst and a preparation method and application thereof. Background Art
[0002] Currently, electrocatalytic water splitting technology (electrolysis of water) is considered to be one of the cleanest energy conversion technologies. This technology includes the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). The electrocatalysts used in these two reactions are mainly precious metals with small reserves and high costs, which hinders the development of electrolysis of water technology.
[0003] NiFe-LDH material is relatively low in cost and is one of the catalysts with excellent OER performance in alkaline media. The development and utilization of NiFe-LDH materials is a current research hotspot. However, NiFe-LDH has poor performance in catalyzing HER, making it difficult for NiFe-LDH to be used as a bifunctional water electrolysis catalyst for OER and HER, increasing the complexity of hydrogen energy equipment design and preparation.
[0004] Based on this, developing a bifunctional water electrolysis catalyst that can be used for OER and HER to reduce the cost of hydrogen production by water electrolysis is a problem that needs to be solved urgently. Summary of the invention
[0005] The present invention provides a method for preparing a bifunctional water electrolysis catalyst. The method can prepare an OER and HER bifunctional water electrolysis catalyst and reduce the cost of hydrogen production by water electrolysis.
[0006] The present invention also provides a bifunctional water electrolysis catalyst, which is prepared by the above method. The bifunctional water electrolysis catalyst can be used as a catalyst for OER and HER at the same time, thereby reducing the cost of raw materials and hydrogen energy equipment.
[0007] The present invention further provides a method for producing hydrogen by electrolysis of water. When the bifunctional water electrolysis catalyst is used as an OER and HER catalyst for water electrolysis reaction, the catalytic activity and catalytic stability are excellent.
[0008] The present invention provides a method for preparing a bifunctional water electrolysis catalyst, comprising:
[0009] 1) Make nickel source, iron source, CeO 2 The mixture of , alkali source and water undergoes hydrothermal reaction to obtain NiFe-LDH / CeO 2 Composite materials;
[0010] 2) Using foam metal as a carrier, using a binder and a dispersant to form the NiFe-LDH / CeO 2 The composite material was loaded onto the foam metal to obtain NiFe-LDH / CeO2 / Foam metal catalyst;
[0011] Among them, the nickel source, iron source, CeO 2 The molar ratio of NiFe-LDH / CeO is (2-4):1:(0.5-0.8); 2 The mass volume ratio of the composite material, the binder and the dispersant is (5-10) mg: (0.05-0.1) mL: (0.5-1.5) mL.
[0012] According to one embodiment of the present invention, the alkali source includes sodium hydroxide and sodium carbonate.
[0013] According to one embodiment of the present invention, the binder includes naphthol, and the dispersant includes anhydrous ethanol.
[0014] According to one embodiment of the present invention, step 1) comprises: 2 Dispersed in water to form a dispersion, an aqueous solution of an alkali source and a mixed aqueous solution of a nickel source and an iron source are simultaneously added to the dispersion, and after the addition is completed, the hydrothermal reaction is performed to obtain the NiFe-LDH / CeO 2 Composite materials;
[0015] The pH of the dispersion was controlled to be 9.5-10.5 during the dropwise addition.
[0016] According to one embodiment of the present invention, the NiFe-LDH / CeO 2 The mass volume ratio of the composite material to the foam metal is (0.005-0.01) g: (2-3) cm 3 .
[0017] According to one embodiment of the present invention, the CeO 2 Including cubic CeO 2 .
[0018] According to one embodiment of the present invention, step 2) comprises: mixing the binder, dispersant and NiFe-LDH / CeO 2 The mixture of the composite materials is loaded onto the foam metal through air flow, and then freeze-dried to obtain the NiFe-LDH / CeO 2 / Foam metal catalyst;
[0019] The air flow rate is 1-3m; the freeze-drying temperature is -20 to -10°C, and the time is 3-6h.
[0020] According to one embodiment of the present invention, the temperature of the hydrothermal reaction is 120-150° C. and the time is 12-24 hours.
[0021] The present invention also provides a bifunctional water electrolysis catalyst, which is prepared by any of the above-mentioned preparation methods. The bifunctional water electrolysis catalyst can be used as an OER and HER catalyst at the same time, effectively reducing the cost of raw materials and hydrogen energy equipment.
[0022] The present invention also provides a method for producing hydrogen by electrolyzing water. When the bifunctional water electrolysis catalyst is used as a catalyst for OER and HER, it has high catalytic activity and stability.
[0023] In the preparation method of the present invention, CeO is in situ embedded in NiFe-LDH. 2 , and then embed CeO 2 The NiFe-LDH is loaded on the foam metal through a binder and a dispersant, and the Ni source, Fe source, CeO 2 The molar ratio of NiFe-LDH / CeO 2 , the mass volume ratio of the binder and the dispersant is such that the obtained NiFe-LDH / CeO 2 / The foamed metal catalyst can act as both OER and HER catalysts, thus reducing the cost of hydrogen production by water electrolysis. Moreover, the bifunctional water electrolysis catalyst prepared by this method also has high catalytic activity and catalytic stability, providing an effective design idea for the development of low-cost, high-activity bifunctional water electrolysis catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1a The cubic CeO prepared in Example 1 2 SEM images of
[0025] Figure 1b1 The NiFe-LDH / CeO prepared in Example 1 2 SEM image of the composite material at 200nm scale;
[0026] Figure 1b2 The NiFe-LDH / CeO prepared in Example 1 2 SEM image of the composite material at 100nm scale;
[0027] Figure 1c1 The NiFe-LDH / CeO prepared in Example 8 2 SEM image of the composite material at 200nm scale;
[0028] Figure 1c2 The NiFe-LDH / CeO prepared in Example 8 2 SEM image of the composite material at 100nm scale;
[0029] Figure 1d1This is a SEM image of the NiFe-LDH composite material prepared in Comparative Example 1 at a scale of 200 nm;
[0030] Figure 1d2 This is a SEM image of the NiFe-LDH composite material prepared in Comparative Example 1 at a scale of 100 nm;
[0031] Figure 2a and Figure 2b The NiFe-LDH / CeO prepared in Example 1 2 TEM image of the composite material at 100 nm;
[0032] Figure 2c The NiFe-LDH / CeO prepared in Example 1 2 HRTEM image of the composite material at 10 nm scale;
[0033] Figure 2d The NiFe-LDH / CeO prepared in Example 1 2 HRTEM image of the composite material at 5nm scale;
[0034] Figure 3 The NiFe-LDH / CeO prepared in Example 1 2 XRD spectra of the composite material and the NiFe-LDH composite material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0036] The first aspect of the present invention provides a method for preparing a bifunctional water electrolysis catalyst, comprising:
[0037] 1) Make nickel source, iron source, CeO 2 The mixture of , alkali source and water undergoes hydrothermal reaction to obtain NiFe-LDH / CeO 2 Composite materials;
[0038] 2) Using foam metal as carrier, NiFe-LDH / CeO 2 The composite material was loaded onto the foam metal to obtain NiFe-LDH / CeO 2 / Foam metal catalyst;
[0039] Among them, nickel source, iron source, CeO 2 The molar ratio of NiFe-LDH / CeO is (2-4):1:(0.5-0.8); 2 The mass volume ratio of the composite material, the binder and the dispersant is (5-10) mg: (0.05-0.1) mL: (0.5-1.5) mL.
[0040] The nickel source includes nickel nitrate hexahydrate, nickel sulfate hexahydrate, and nickel chloride, and the iron source includes ferric nitrate nonahydrate, ferric sulfate, and ferric chloride.
[0041] The above step 1) can convert CeO 2 In situ embedded in NiFe-LDH (nickel-iron binary hydrotalcite).
[0042] The above-mentioned foam metal includes foam nickel (NF), foam copper, and foam titanium. In consideration of the preparation cost and the corrosion resistance of the catalyst, foam nickel is preferred.
[0043] The above step 2) can convert NiFe-LDH / CeO 2 The composite material is loaded on the foam metal. Among them, Ni, Fe and CeO 2 As active ingredient.
[0044] The catalyst prepared by the above method can be used to catalyze OER and HER at the same time, without the need for complex design of hydrogen energy equipment or the use of expensive precious metal raw materials, effectively reducing the cost of hydrogen production by electrolysis of water. At the same time, the bifunctional water electrolysis catalyst prepared by this method also has excellent catalytic activity and catalytic stability.
[0045] The inventors analyzed that the catalyst can be used for catalyzing both OER and HER because Ni and Fe have OER performance and CeO 2 After that, on the one hand, CeO 2 Oxygen vacancy defects are beneficial to HER performance; on the other hand, CeO 2 The interfaces between Ni and Fe components can also provide HER active sites.
[0046] Furthermore, the catalyst prepared by the above method also has excellent catalytic activity and catalytic stability because: on the one hand, the active components Ni, Fe, CeO 2 It is easy to aggregate and CeO 2 In situ growth on NiFe-LDH can avoid its aggregation, give full play to the catalytic activity and improve the catalytic stability; at the same time, CeO 2 In situ growth on NiFe-LDH can also enhance the electron transfer and ion transport capabilities during electrocatalysis, and in the process of water electrolysis, CeO2 The Ce in the electrolyte can be converted between trivalent and tetravalent, and store and release oxygen, which is beneficial to the catalytic activity. On the other hand, the foamed metal as a carrier can greatly enhance the conductivity and stability of the material, and make the catalyst have a mesoporous structure and a large specific surface area, exposing more active sites, accelerating the contact between the active components and the electrolyte, and further improving the catalytic activity.
[0047] The inventors found that when the nickel source, iron source, CeO 2 When the molar ratio is (2-4):1:(0.5-0.8), the water electrolysis catalyst has relatively excellent catalytic performance. When this molar ratio is not met, the catalytic activity and catalytic stability will be reduced, which may be caused by the interaction between electrons.
[0048] Furthermore, when controlling NiFe-LDH / CeO 2 When the mass volume ratio of the composite material, the binder and the dispersant is (5-10) mg: (0.05-0.1) mL: (0.5-1.5) mL, NiFe-LDH / CeO 2 The composite material is evenly and firmly loaded on the surface of the foam metal to avoid the Ni, Fe, CeO 2 The problem of reduced catalytic activity or stability due to uneven loading or shedding.
[0049] It should be noted that after the hydrothermal reaction is completed, the obtained product needs to be washed alternately with water and anhydrous ethanol to remove impurities in the product such as carbonate impurities, nickel-iron oxides, etc. The present invention does not limit the number of washings, as long as the impurities in the reaction product can be eliminated. The washed product is dried to obtain NiFe-LDH / CeO 2 Composite materials.
[0050] According to the inventor's research, when the alkali source includes sodium hydroxide (NaOH) and sodium carbonate (Na 2 CO3), CeO 2 It can be more firmly embedded in NiFe-LDH, which is beneficial to improving the catalytic stability of the water electrolysis catalyst.
[0051] In a specific implementation process, the binder includes naphthol, and the dispersant includes anhydrous ethanol.
[0052] The combination of the above binder and dispersant can make NiFe-LDH / CeO 2 The composite material is uniformly, quickly and firmly loaded on the metal foam, further improving the catalytic activity and catalytic stability of the water electrolysis catalyst.
[0053] In the present invention, step 1) comprises: 2Dispersed in water to form a dispersion, an aqueous solution of an alkali source and a mixed aqueous solution of a nickel source and an iron source are simultaneously added to the dispersion, and a hydrothermal reaction is performed after the addition is completed to obtain NiFe-LDH / CeO 2 Composite materials;
[0054] The pH of the dispersion was controlled to be 9.5-10.5 during the dropwise addition.
[0055] The above process can make Ni, Fe, CeO 2 Uniform dispersion, followed by hydrothermal reaction, forms NiFe-LDH / CeO with regular morphology. 2 Composite materials.
[0056] When dropping the aqueous solution of the alkali source and the mixed aqueous solution of the nickel source and the iron source, the pH of the dispersion needs to be controlled to 9.5-10.5 to ensure that Ni and Fe can be evenly precipitated on the CeO 2 Therefore, it is beneficial to form NiFe-LDH / CeO with regular morphology. 2 Composite materials.
[0057] In specific implementation, NiFe-LDH / CeO 2 The mass volume ratio of composite material to foam metal is (0.005-0.01)g: (2-3)cm 3 At this mass-to-volume ratio, the foam metal can be loaded with sufficient active components, giving full play to the synergistic effect of the foam metal and the active components on catalytic activity and catalytic stability.
[0058] In the present invention, CeO 2 Including cubic CeO 2 . Cubic CeO 2 Its unique morphology enables it to be firmly embedded between NiFe-LDH and is not easy to fall off, which is beneficial to improve the catalytic activity and catalytic stability. 2 , select cubic CeO 2 The improvement effect on catalytic performance is better.
[0059] In specific implementation, cubic CeO 2 The preparation method is as follows: cerium nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 The mixed solution of aqueous solution of CeO2 and aqueous solution of sodium hydroxide was ultrasonically treated for 20-30 minutes, and then placed at 150-180°C for hydrothermal reaction for 24-30 hours. After washing with water and anhydrous ethanol alternately, it was dried and then calcined at 600-650°C for 120 minutes to obtain cubic CeO2. 2 ; Among them, Ce(NO 3 )3 6H 2 The molar ratio of O to sodium hydroxide is 1:120, Ce(NO 3 ) 3 6H 2 The concentration of the aqueous solution of O was 0.01 g / mL, and the concentration of the aqueous solution of sodium hydroxide was 0.32 g / mL.
[0060] The above step 2) comprises: mixing a binder, a dispersant and NiFe-LDH / CeO 2 The mixture of the composite materials was loaded onto the foam metal by air flow and then freeze-dried to obtain NiFe-LDH / CeO 2 / Foam metal catalyst;
[0061] The air flow rate is 1-3m; the freeze-drying temperature is -20 to 10°C, and the time is 3-6h.
[0062] NiFe-LDH / CeO 2 The composite material is loaded on the foam metal, which is conducive to uniformly loading the active components on the foam metal. In specific implementation, when the flow rate of the air flow is controlled to be 1-3m, the active components can be uniformly loaded on the foam metal more quickly.
[0063] Preparation of NiFe-LDH / CeO by freeze drying 2 / Foamed metal catalysts can maintain the pore structure of the catalyst, CeO 2 The embedded structure and NiFe-LDH structure are beneficial to improving the catalytic activity and catalytic stability of the catalyst. In specific implementation, when the freeze-drying temperature is controlled to be -20 to -10°C and the time is 3 to 6 hours, a catalyst with better morphology can be obtained in a relatively short time.
[0064] In the present invention, the temperature of the hydrothermal reaction is 120-150° C. and the time is 12-24 hours.
[0065] The second aspect of the present invention provides a bifunctional water electrolysis catalyst, which is prepared by any of the aforementioned methods. The bifunctional water electrolysis catalyst is relatively low in cost and can be used as both an OER and HER catalyst.
[0066] The third aspect of the present invention provides a method for producing hydrogen by electrolysis of water, using the above-mentioned bifunctional water electrolysis catalyst as an OER and HER catalyst. In the specific implementation process, the present invention selects 1M KOH as the electrolyte, and the inventors can of course also select other types of electrolytes, such as 1M NaOH, etc. When water is electrolyzed by the above method, only 1.68V battery voltage is required to obtain 10mA / cm 2 The current is 10mA / cm2 After electrolysis for 100 hours at a current of , the current density can still be maintained as high as 96%.
[0067] The present invention is described in more detail below through specific examples.
[0068] Example 1
[0069] 1) Cubic CeO 2 Preparation
[0070] Will Ce(NO 3 ) 3 6H 2 The mixed solution of aqueous solution of CeO and aqueous solution of NaOH was ultrasonically treated for 30 min, then placed at 180 °C for hydrothermal reaction for 24 h, washed alternately with water and anhydrous ethanol, dried, and then calcined at 600 °C for 120 min to obtain cubic CeO 2 ;
[0071] Among them, Ce(NO 3 ) 3 6H 2 The molar ratio of O to NaOH is 1:120, Ce(NO 3 ) 3 6H 2 The concentration of the aqueous solution of O is 0.01 g / mL, and the concentration of the aqueous solution of NaOH is 0.32 g / mL;
[0072] 2) NiFe-LDH / CeO 2 Preparation of composite materials
[0073] 0.05 g CeO 2 Dispersed in 10 mL of water to form a dispersion;
[0074] 0.44 g Ni(NO 3 ) 2 6H 2 O and 0.20 g Fe(NO 3 ) 3 9H 2 O is dissolved in 25 ml of water to form a mixed solution of nickel source and iron source;
[0075] 0.50 g NaOH and 1.3 g Na 2 CO 3 Dissolve in 25 ml of water to form an aqueous solution of alkaline source;
[0076] The aqueous solution of the alkali source, the nickel source and the mixed aqueous solution of the iron source are simultaneously added to the dispersion, and the pH of the dispersion is controlled to be 10 during the dropping process. After the dropping is completed, the dispersion is subjected to a hydrothermal reaction at 120° C. for 12 hours, and then washed alternately with water and anhydrous ethanol and dried to obtain NiFe-LDH / CeO 2 Composite materials;
[0077] Among them, nickel source, iron source, CeO 2 The molar ratio is 3:1:0.6;
[0078] 3) NiFe-LDH / CeO 2 Preparation of Nickel Foam (NF) Catalyst
[0079] NiFe-LDH / CeO 2 The composite material was mixed with naphthol solution and anhydrous ethanol and loaded onto a 1×3×0.2cm 3 NiFe-LDH / CeO was obtained after freeze drying at -15℃ for 6h. 2 / NF catalyst;
[0080] Among them, NiFe-LDH / CeO 2 The mass volume ratio of composite material, binder and dispersant is 5 mg: 0.05 mL: 1 mL, NiFe-LDH / CeO 2 The mass volume ratio of the composite material to the foam metal is 0.005g:3cm 3 .
[0081] Example 2
[0082] The difference between this embodiment and embodiment 1 is that the alkali source is sodium hydroxide, and the other conditions are the same as those in embodiment 1.
[0083] Example 3
[0084] The difference between this embodiment and embodiment 1 is that the alkali source is sodium carbonate, and the other conditions are the same as those in embodiment 1.
[0085] Example 4
[0086] The difference between this embodiment and embodiment 1 is that the dispersant is water.
[0087] Example 5
[0088] The difference between this embodiment and embodiment 1 is that the adhesive is conductive carbon glue.
[0089] Example 6
[0090] The difference between this embodiment 1 and embodiment 1 is that the pH is controlled to be 12 when the aqueous solution of the alkali source and the mixed aqueous solution of the nickel source and the iron source are added dropwise.
[0091] Example 7
[0092] The difference between this embodiment and embodiment 1 is that NiFe-LDH / CeO 2 The mass volume ratio of the composite material to the foam metal is 0.015g:3cm 3 .
[0093] Example 8
[0094] The difference between this embodiment and embodiment 1 is that CeO 2 For nanorods.
[0095] Example 9
[0096] The difference between this embodiment and embodiment 1 is that in step 2), CeO 2 The aqueous solution of the alkali source, the mixed aqueous solution of the nickel source and the iron source are simultaneously added to the dispersion of the present invention, and the pH of the dispersion is controlled to be 9.5 during the dropping process. After the dropping is completed, the dispersion is subjected to a hydrothermal reaction at 120° C. for 24 hours, and then the dispersion is washed alternately with water and anhydrous ethanol and then dried to obtain NiFe-LDH / CeO 2 Composite materials;
[0097] Among them, nickel source, iron source, CeO 2 The molar ratio is 4:1:0.8;
[0098] In step 3), NiFe-LDH / CeO 2 The composite material was mixed with naphthol solution and anhydrous ethanol and loaded onto a 1×3×0.2cm 3 After freeze drying at -20 °C for 3 h, NiFe-LDH / CeO 2 / Foam copper catalyst;
[0099] Among them, NiFe-LDH / CeO 2 The mass volume ratio of composite material, binder and dispersant is 10 mg: 0.1 mL: 1.5 mL, NiFe-LDH / CeO 2 The mass volume ratio of the composite material to the foam metal is 0.01g:3cm 3 .
[0100] Comparative Example 1
[0101] The difference between this comparative example and Example 1 is that no CeO is added. 2 , NiFe-LDH composite material was first prepared, and then NiFe-LDH / NF catalyst was further prepared.
[0102] Comparative Example 2
[0103] The difference between this comparative example and Example 1 is that no binder and dispersant are used, and the foam metal is immersed in a mixture containing a nickel source, an iron source, and CeO 2 In a mixture of alkali source and water, a hydrothermal reaction was carried out to obtain NiFe-LDH / CeO 2 / NF catalyst.
[0104] Comparative Example 3
[0105] The difference between this comparative example and Example 1 is that NiFe-LDH / CeO 2 The composite material was loaded on nickel foam to directly obtain NiFe-LDH / CeO 2 catalyst.
[0106] Comparative Example 4
[0107] The difference between this comparative example and Example 1 is that the nickel source, iron source, CeO 2 The molar ratio of NiFe-LDH / CeO was 6:1:1. 2 / NF catalyst.
[0108] Comparative Example 5
[0109] The difference between this comparative example and Example 1 is that NiFe-LDH / CeO 2 The mass volume ratio of the composite material, binder, and dispersant was 12 mg: 0.2 mL: 2 mL, and NiFe-LDH / CeO 2 / NF catalyst.
[0110] Test Example 1
[0111] The cubic CeO prepared in Example 1 of the present invention was characterized by SEM (scanning electron microscope). 2 , NiFe-LDH / CeO prepared in Example 1 and Example 8 2 Composite material, and the micromorphology of the NiFe-LDH composite material prepared in Comparative Example 1. Figure 1a The CeO prepared in Example 1 of the present invention 2 SEM images of Figure 1b1 , Figure 1b2 The NiFe-LDH / CeO obtained in Example 1 2 SEM images of the composite material at 200nm scale and 100nm scale. Figure 1c1 , Figure 1c2 The NiFe-LDH / CeO prepared in Example 8 2 SEM images of the composite material at 200nm scale and 100nm scale. Figure 1d1 and Figure 1d2These are SEM images of the NiFe-LDH prepared in Comparative Example 1 at 200 nm and 100 nm scales.
[0112] As can be seen from the figure, the present invention successfully prepared cubic CeO 2 Compared with comparative example 1, in example 1 of the present invention, cubic CeO 2 Example 8: Rod-shaped CeO is uniformly grown on the nickel-iron binary hydrotalcite nanosheets. 2 This indicates that the present invention successfully converts CeO 2 It is embedded in the NiFe-LDH structure and is uniformly embedded, which is beneficial to improving the catalytic performance.
[0113] Test Example 2
[0114] The NiFe-LDH / CeO prepared in Example 1 of the present invention was characterized by TEM (transmission electron microscopy) and HRTEM (high resolution transmission electron microscopy). 2 The microstructure of the composite material is shown in Figure 2. Figure 2a , Figure 2b The NiFe-LDH / CeO prepared in Example 1 2 TEM image of the composite material at 100nm. Figure 2c , Figure 2d They are NiFe-LDH / CeO prepared in Example 1. 2 HRTEM images of the composite material at 10nm and 5nm scales.
[0115] according to Figure 2a and Figure 2b It can be seen that the NiFe-LDH / CeO prepared in Example 1 of the present invention 2 In composite materials, CeO 2 The nanoparticles grow evenly on the well-organized NiFe-LDH nanosheets and rarely aggregate, which indicates that NiFe-LDH nanosheets can avoid CeO 2 The nanoparticles agglomerate, and at the same time, the Ni and Fe on the NiFe-LDH nanosheets are also fixed and are not easy to aggregate.
[0116] Figure 2c and Figure 2d The lattice fringes are CeO 2 The (222) crystal plane and CeO 2 The (220) crystal plane has a lattice spacing of 0.156 nm and a lattice spacing of 0.191 nm, which further indicates that CeO 2 Successfully embedded in NiFe-LDH nanosheets.
[0117] Test Example 3
[0118] The NiFe-LDH / CeO prepared in Example 1 of the present invention was characterized by XRD (X-ray diffraction) patterns. 2 The crystallization of the composite material and the NiFe-LDH composite material prepared in Comparative Example 1. Figure 3 .
[0119] according to Figure 3 It can be seen that compared with Comparative Example 1, Example 1 of the present invention adds CeO 2 The diffraction peaks of the standard (JCPDS78-0694) are highly consistent, which once again shows that the present invention successfully introduced CeO 2 .
[0120] Test Example 4
[0121] The catalysts prepared in Examples 1-9 and Comparative Examples 1-5 of the present invention were used as OER and HER catalysts to produce hydrogen by electrolysis of water in 1.0 M KOH. 2 The lower cell potential indicates the catalytic activity of the water electrolysis catalyst; at 10 mA / cm 2 The catalytic stability of the water electrolysis catalyst was tested by testing the retention rate of the battery current density after 100 hours compared to the initial current density. The results are shown in Table 1.
[0122] Table 1 Catalytic activity and catalytic stability of catalysts
[0123] sample Battery potential (V) Current density retention rate (%) Example 1 1.68 96 Example 2 1.72 94 Example 3 1.75 90 Example 4 1.69 93 Example 5 1.77 86 Example 6 1.73 93 Example 7 1.70 90 Example 8 1.78 81 Example 9 1.75 89 Comparative Example 1 / / Comparative Example 2 1.85 77 Comparative Example 3 1.93 64 Comparative Example 4 1.83 90 Comparative Example 5 1.82 91
[0124] It can be seen from Table 1 that when the catalysts of Examples 1-9 of the present invention are used as bifunctional water electrolysis catalysts, the battery potential can be as low as 1.68 V, and the current density retention rate can be as high as 96%, and they have excellent catalytic activity and catalytic stability.
[0125] The inventors have found through experiments that comparative example 1 cannot be used as a HER and OER bifunctional water electrolysis catalyst, while the catalysts prepared in Examples 1-9 of the present invention can all be used as HER and OER bifunctional water electrolysis catalysts. In addition, when the catalysts of comparative examples 2-5 are used as OER and HER bifunctional water electrolysis catalysts, a higher cell potential is required, and when the foam metal is not introduced (Comparative example 3) or the foam metal is directly composited with a nickel source, an iron source, and a cerium source hydrothermally in situ (Comparative example 2), the catalytic stability is poor.
[0126] Compared with Examples 2-8, the catalyst prepared in Example 1 has higher catalytic activity and stability, which shows that, compared with selecting sodium hydroxide and sodium carbonate as alkali sources respectively (Examples 2 and 3), selecting both as alkali sources is more conducive to obtaining a catalyst with excellent performance; compared with selecting other types of dispersants or binders (Examples 4 and 5), when naphthol and ethanol are selected as dispersants and binders at the same time, the performance of the catalyst is more excellent; in addition, selecting cubic CeO 2 , control NiFe-LDH / CeO 2 The mass volume ratio of composite material to foam metal is (0.005-0.01)g: (2-3)cm 3 , and controlling the pH of the aqueous solution of the added alkali and the mixed aqueous solution of the nickel source and iron source to 9.5-10.5 are all beneficial to obtaining a catalyst with good catalytic activity and catalytic stability.
[0127] In order to make the purpose, technical solution and advantages of the present invention clearer, the above-mentioned technical solution of the present invention is clearly and completely described in combination with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a bifunctional water electrolysis catalyst, characterized in that: include: 1) causing a mixture including a nickel source, an iron source, CeO2, an alkali source and water to undergo a hydrothermal reaction to obtain a NiFe-LDH / CeO2 composite material; 2) using a foam metal as a carrier, and using a binder and a dispersant to load the NiFe-LDH / CeO2 composite material onto the foam metal to obtain a NiFe-LDH / CeO2 / foam metal catalyst; The molar ratio of the nickel source, the iron source and CeO2 is (2-4):1:(0.5-0.8); the mass volume ratio of the NiFe-LDH / CeO2 composite material, the binder and the dispersant is (5-10) mg:(0.05-0.1) mL:(0.5-1.5) mL; The alkali source includes sodium hydroxide and sodium carbonate; The binder includes naphthol, and the dispersant includes anhydrous ethanol.
2. The preparation method according to claim 1, characterized in that: Step 1) comprises dispersing the CeO2 in water to form a dispersion, simultaneously adding the aqueous solution of the alkali source and the mixed aqueous solution of the nickel source and the iron source to the dispersion, and performing the hydrothermal reaction after the addition is completed to obtain the NiFe-LDH / CeO2 composite material; The pH of the dispersion was controlled to be 9.5-10.5 during the dropwise addition.
3. The preparation method according to any one of claims 1 to 2, characterized in that: The mass volume ratio of the NiFe-LDH / CeO2 composite material to the foam metal is (0.005-0.01) g: (2-3) cm 3 .
4. The preparation method according to any one of claims 1 to 2, characterized in that: The CeO2 includes cubic CeO2.
5. The preparation method according to any one of claims 1 to 2, characterized in that: Step 2) comprises: loading the mixture of the binder, the dispersant and the NiFe-LDH / CeO2 composite material onto a foam metal through air flow, and then freeze-drying to obtain the NiFe-LDH / CeO2 / foam metal catalyst; The air flow rate is 1-3m; the freeze-drying temperature is -20 to -10°C, and the time is 3-6h.
6. The preparation method according to any one of claims 1-2, characterized in that: The temperature of the hydrothermal reaction is 120-150° C. and the time is 12-24 hours.
7. A bifunctional water electrolysis catalyst, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.
8. A method for producing hydrogen by electrolysis of water, characterized in that: The water electrolysis catalyst described in claim 7 is used as a catalyst for OER and HER.
Citation Information
Patent Citations
Bifunctional electrolyzed water catalyst as well as preparation method and application thereof
CN116905039A